Edukasi Khasiat Obat Tanaman Pekarangan untuk Kesehatan Masyarakat Mitra Taman Hutan Raya Wan Abdurachman Provinsi Lampung - Duryat, Duryat; Dewi, Bainah Sari; Qurniati, Rommy; Bakri, Samsul; Manaf, Latifah Abd.; Rodiani, Rodiani (Jurnal Pengabdian Fakultas Pertanian Universitas Lampung, 2025)
While not yet regulated at the legislative level, traditional medicine therapy has gained legal recognition at the ministerial level through Ministerial Regulation No. 6 of 2016 and No. 37 of 2017. These legal frameworks significantly facilitate scientific exploration for research and practical application of herbal medicine. Promoting such practices is particularly urgent for rural communities that face barriers to accessing modern healthcare services or financial constraints. The community engagement program aimed to introduce medicinal plants growing in situ while reinforcing traditional healing practices already embedded within the local community. Conducted on January 18, 2025, the initiative involved 15 participants, most of whom were women, reflecting inclusive access to educational activities. The core activities comprised lectures and interactive discussions on local biodiversity, medicinal plant identification, cultivation techniques, and traditional herbal processing. Pre- and post-activity evaluations revealed a significant improvement in cognitive knowledge and affective attitudes. The average cognitive scores for topics such as biodiversity awareness and medicinal plant cultivation increased from the "low-moderate" to the "good-excellent" category, while affective scores regarding the perceived benefits of herbal medicine rose from "poor" to "excellent." Participants'